The value of trace minerals in a wintering and fattening ration. Self-feeding grain in dry lot vs. self-feeding grain on bluestem pasture. - Smith, E.F.; Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
This is a report of the wintering phase of this test. Following this phase the different lots will be grazed together on bluestem pasture and then full-fed grain until they grade choice. One objective of the test is to find out the effect of trace mineralized salt containing iodine, copper, cobalt, iron, and manganese on the performance of steer calves on wintering rations and on a full feed of grain. Another phase of the test is to compare self-feeding grain in dry to self-feeding grain on grass for calve handled in the deferred full-feeding program. The system of deferred full-feeding using good quality steer claves consists of three phases: (1) producing 225-250 pounds of gain during the winter; (2) grazing 90 days without grain; (3) full-feeding 100 days in the dry lot.
Keywords: Beef; Trace minerals; Gain; Dry lot vs self-feeding grain